The effects of inquiry-based information literacy instruction on memory and comprehension: A longitudinal study - Chen, Lin Ching; Huang, Tsai-Wei; Chen, Yaw-Huei (Library & information science research, 2017)
How information literacy instruction affects students' learning has been a concern for many librarians and teachers. This study examines the effects of six-year integrated information literacy instruction on elementary students' memory and comprehension of subject content through inquiry learning and also focuses on the moderating factor of students' academic achievement levels. The subjects were 75 students participating in the study from the time when they entered elementary school. The school adopted information literacy instruction and integrated it into various subject areas using the framework of inquiry learning, for example, the Super3 and Big6 models. A total of 11 inquiry learning projects were implemented from Grade 1 through Grade 6. The results showed that inquiry-based integrated information literacy instruction helps students memorize facts and apply new concepts in the subject content. In general, the progress level in comprehension was higher than in memory learning for the six-year integrated information literacy instruction. Regardless of students' prior academic achievement levels, if they devoted their efforts to inquiry processes, their fact memorization and conceptual understanding of subject content improved. Low-achieving students displayed the most progression in both memory and comprehension learning, compared to their medium- and high-achieving peers. This study underscores the importance of information literacy instruction in students' learning. •This study examines the effects of six-year integrated information literacy instruction on elementary students' learning.•Inquiry-based information literacy instruction can help elementary students in memory learning and comprehension learning.•Inquiry-based learning is better for comprehension learning than memory learning at elementary grade levels.•Low-achieving students display most progress in both memory and comprehension learning than medium- or high-achieving ones.•Researchers collaborated with teachers and librarians to develop inquiry-based information literacy instruction.